Improving the health of cisgender men who identify as bisexual: What do they want from interventions? - Feinstein, Brian A. (Sex Res Social Policy, 2019)
Self-identified bisexual men are at increased risk for negative health outcomes, but there are no interventions tailored to their unique needs. In order to develop interventions for this population, it is first necessary to understand their preferences. As part of a larger study, 128 cisgender men who identified as bisexual reported on their preferences for different intervention components. Large proportions of participants prioritized addressing both health (e.g., mental health, HIV/STI) and psychosocial experiences (e.g., dating/relationships, discrimination/victimization). A slightly larger proportion of participants preferred an intervention for gay and bisexual men together compared to an intervention for bisexual men only. However, those who reported more discrimination and recent female sexual partners were more likely to prefer an intervention for bisexual men only. Larger proportions of participants preferred a group intervention compared to an individual intervention and an in-person intervention compared to an online intervention. These findings highlight the importance of addressing both health and psychosocial experiences in tailored interventions for self-identified bisexual men. Further, while in-person and group interventions may appeal to larger proportions of self-identified bisexual men, the appeal of an intervention for gay and bisexual men together compared to an intervention for bisexual men only may depend on individual and social/contextual factors.